Following the Science by Roger A. Pielke Sr. - Roger A. Pielke Sr. (Perspectives of Earth and Space Scientists)
Abstract The pursuit of basic knowledge and conveying that knowledge for the benefit of society is one of the most rewarding endeavors of life. The opportunity to devote one's professional life to science in order to learn and create new knowledge is intoxicating. This short article highlights some of the aspects of my career that perhaps students and others will find useful, including life experiences that directly affected my career. I also suggest opportunities for major advances in our understanding and predictability of Earth system processes.